Dynamic Cause of the Sudden Death Event of Small Yellow Croaker (Larimichthys polyactis) in the East China Sea in Winter 2017 - Zilu Wei; Xiaohui Jiao; Jicai Zhang; Yunfei Du; Zengrui Rong; Hui Wu; Ya Ping Wang (Frontiers in Marine Science, 2022)
Small yellow croaker ( Larimichthys polyactis ), a benthic fish species widely distributed in the Northwest Pacific Ocean, plays an important role in the fishery catch of coastal countries. A large amount of dead small yellow croaker floated on the sea surface near 30.2°N, 125.3°E in the East China Sea on 19 February 2017, and more than 9,000 kilograms were caught by fishermen, which had never been recorded before. This study aims to investigate the dynamic causes of this sudden death event based on available in-situ, satellite and modelling data. The event occurred near the overwintering ground of small yellow croaker, where a majority of these fish assembled in winter. There were persistent ocean fronts at target site with average intensity of 0.05°C/km at sea surface and bottom in February 2017, which was the strongest in the past 5 years from 2015 to 2019. The fronts provided nutrients and food to fish, and the intense gradients prevented fish from crossing, thus forming “water barriers” to restrict the horizontal movement of fish. Due to enhanced convection, the water was well-mixed, enabling the demersal croaker to float to sea surface. The sea temperature was particularly warm in winter 2017, but then experienced a significant drop by more than 4.5°C in 40 days according to satellite and modelling datasets due to the northerly wind and the southeastward movement of cold eddy. The drop of temperature led to ‘cold shock’ of fish, affecting their physiological regulation and survival. Under the combined influence of these factors, a large number of small yellow croaker died and aggregated near the target site. This paper has a great reference value for further study on the living habits of small yellow croaker and their responses to marine dynamic changes.